Zolpidem’s insidious potential of abuse: A word of caution - Husnain, Ali; Qadeer, Abdul; Tanvir, Khadija; Nadeem, Arsalan (Journal of the Pakistan Medical Association, 2024)
To the Editor, Zolpidem is a sedative-hypnotic drug with a binding site similar to benzodiazepines (BZ) and is commonly used in the treatment of insomnia. Initial clinical trials have demonstrated promising results, and the drug was marketed because of its efficacy, low dependence risk, and safer profile.1,2,3 However, several studies have highlighted a serious concern about the misuse of non-BZ drugs, demonstrating that the usage of zolpidem is associated with complex sleep behaviours, including somnambulism, falls with serious injuries, motor vehicle accidents, attempted suicide, inability to recall actions taken while asleep, and even death in a few cases.3 The US Food and Drug Administration (FDA) has brought attention to this concern with a boxed warning.3 One peculiar side effect of zolpidem is euphoria and a state of being high. A 2007 network study spotlighted this effect of zolpidem in several instances of drug abuse when a population group consumed the substance for stimulation, feelings of well-being and euphoria, anxiolysis, and sexual disinhibition.2 More recently, a 2022 case study reported this paradoxical effect in a 23-year-old female who was prescribed zolpidem for trouble with sleeping but later discovered the euphoric effects of the drug by chance, which led to her ingesting increasing doses, ultimately resulting in dependence, withdrawal symptoms, depressive mood, and even suicide attempts.4 With prolonged use, mania, delusions, and withdrawal seizures have been reported as well.3 These alarming findings raise a more serious issue: are the existing laws sufficient to protect the public from zolpidem abuse and its harmful side effects? Pakistan is among the nations that frequently utilize zolpidem as it is easily available without prescription and supervision. Zolpidem could be a new alternative for drug abusers or a first drug abuse case for first-time users.5 Unchecked use of such drugs is a result of a lack of awareness about their negative effects, stigma surrounding mental health, lack of rehabilitation facilities, unhealthy lifestyles, and poor sleep hygiene. The Drug Regulatory Authority of Pakistan (DRAP) has issued a drug safety alert urging registration holders to update the safety specification of zolpidem-containing drugs by including information related to complex sleep behaviour in the warning and precautions, information related to contraindications in patients who have experienced complex sleep behaviours after taking these drugs in the past, and to create a boxed warning in accordance with the FDA format. ---Continue